Neighbourhood degree-based graph descriptors: A comprehensive analysis of connectivity patterns in diverse graph families and their applicapability - Alameri, Abdu; Mahboob, Abid; Karash, Emad Toma (Acadlore (Acadlore Publishing Services Limited), 2024)
Alameri, A., Mahboob, A., & Karash, E. T. (2024). Neighbourhood Degree-Based Graph Descriptors: A Comprehensive Analysis of Connectivity Patterns in Diverse Graph Families and Their Applicapability. Acadlore Trans. Appl Math. Stat., 2(1), 52-63. https://doi.org/10.56578/atams020105